2019
DOI: 10.1177/0022429419885931
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships Among Interval Identification, Pitch Error Detection, and Stimulus Timbre by Preservice Teachers

Abstract: We examined the relationship between interval identification skill and error detection skill in preservice teachers, accounting for timbral differences by including piano and vocal stimuli. The interval identification test was comprised of 33 items spanning from C2 to B5. Fifteen error detection items were monophonic melodies, two measures long, in 4/4 meter, and included one pitch error. Music education majors ( N = 50) completed both tests in vocal and piano timbres during one individual study session. Inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 48 publications
1
10
2
1
Order By: Relevance
“…Developing an aural awareness and understanding of intervals has been viewed as fundamental to good musicianship (Buttram, 1969), and has been found to be important for more advanced aural skills. For instance, interval identification is closely related to the skill of sightsinging (Ottman, 1956), and has more recently been shown to predict the detection of pitch errors in musical performance (Stambaugh & Nichols, 2020). Unsurprisingly, music schools often spend enormous amounts of time on interval identification as a common ear-training activity (Rogers, 2004), given that listening skills have been considered "prerequisite to all other musical pursuits" (Madsen & Geringer, 2000-2001.…”
mentioning
confidence: 99%
“…Developing an aural awareness and understanding of intervals has been viewed as fundamental to good musicianship (Buttram, 1969), and has been found to be important for more advanced aural skills. For instance, interval identification is closely related to the skill of sightsinging (Ottman, 1956), and has more recently been shown to predict the detection of pitch errors in musical performance (Stambaugh & Nichols, 2020). Unsurprisingly, music schools often spend enormous amounts of time on interval identification as a common ear-training activity (Rogers, 2004), given that listening skills have been considered "prerequisite to all other musical pursuits" (Madsen & Geringer, 2000-2001.…”
mentioning
confidence: 99%
“…Similarly, Sidnell (1971) reported a weak correlation between second year aural skills course GPA and students’ ability to detect errors during score reading. However, Stambaugh and Nichols (2020) found a high level of correlation between interval identification and pitch error detection in preservice music educators. In addition, Stambaugh (2016) reported that although music theory grades were not significantly correlated with error detection abilities in preservice band and choral music educators, aural skills grades were related to the ability to identify pitch errors outside of one’s primary area (band or chorus).…”
Section: Review Of Literaturementioning
confidence: 81%
“…Because live music performances are likely to contain unintentional errors or music elements that are subject to interpretation (e.g., intonation, balance, blend, and dynamics), many researchers who developed error detection studies created simulated music stimuli to control for these factors. This practice often includes creating sound files through computer notation programs with MIDI playback and/or simplifying playback timbres (Byo, 1993, 1997; Byo & Sheldon, 2000; Crowe, 1996; Schlegel, 2010; Sheldon, 1998; Stambaugh & Nichols, 2020). However, some researchers used authentic listening conditions created by the use of live musicians in real-world ensemble scenarios (Koner, 2012; Ramsey, 1979; Waggoner, 2011).…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Interval identification test. We developed a shortened version of a previously designed test for use (Stambaugh & Nichols, 2020). The previous test included 33 items that were presented aurally to participants.…”
Section: Stimulimentioning
confidence: 99%